Consider the system $$ \dot{x}=y,\qquad\dot{y}=x+x^2-y. $$ It has two equilibria, namely $(0,0)$ and $(-1,0)$.

I would like to linearize the system in both equilibria.

My start is to set $\Delta x=x-x_0,\qquad \Delta y=y-y_0$. Then $$ \dot{\Delta x}=\dot{x}-\dot{x_0}=y-y_0=\Delta y $$ and $$ \dot{\Delta y}=\dot{y}-\dot{y_0}=\Delta x-\Delta y+x^2-x_0^2. $$

How can I get rid of the summand $x^2-x_0^2$?

Can I approximate the function $f(x)=x^2$ by Taylor, getting $x^2-x_0^2\approx 2x_0\Delta x$?

I then would get the linearization matrices $$ \begin{pmatrix}0 & 1\\ 1 & -1\end{pmatrix}\text{ for }(0,0) $$ and, similarly, $$ \begin{pmatrix}0 & 1\\-1 & -1\end{pmatrix}\text{ for }(-1,0). $$

  • $\begingroup$ You also can write $x^2 - x_0^2 = (x-x_0)(x+x_0) = \Delta x ( (x-x_0) + 2x_0) = \Delta x (\Delta x + 2x_0)$ and after that throw away all terms of higher order in $\Delta x$. $\endgroup$ – Evgeny Jan 3 '16 at 13:42

I will do the general case.

Let $F:\mathbb{R}^n\to\mathbb{R}^n$ be a smooth map. Consider the differential equation on $\mathbb{R}^n$ given by $$\dot{z} = F(z).$$ An equilibrium point is a point $z_0\in\mathbb{R}^n$ where $F(z_0)=0$. This implies that $z(t)=z_0$ is a solution of the differential equation. The linearization of the differential equation at any point is given by taking the Taylor series of $F$ in the right hand side and cutting it off after the linear term. If you are at an equilibrium point, then the constant term is zero and you get $$\dot{z}=D_{z_0}F(z).$$ This gives a good approximation for the behavior of solutions of the original differential equation near an equilibrium point.

In your special case, we have $$F\pmatrix{x\\y} = \pmatrix{y\\x^2+x-y}.$$ Therefore, the matrices you obtain are $$D_{(0,0)}F = \pmatrix{0&1\\1&-1},\qquad D_{(-1,0)}F=\pmatrix{0&1\\-1&-1},$$ which agrees with your solution.

  • $\begingroup$ I won't say that OP has error in the procedure. His derivation is perfectly right in case when $(x_0(t), y_0(t))$ is non-equilibrium trajectory and is still valid when it is an equilibrium. It's just another way to derive these equations. $\endgroup$ – Evgeny Jan 3 '16 at 13:33
  • $\begingroup$ @Evgeny Right, edited thanks. $\endgroup$ – Daniel Robert-Nicoud Jan 3 '16 at 13:45

No, that is wrong. $x_0$ and $y_0$ are constants, only $Δx$ and $Δy$ are functions of $t$. Thus \begin{align} (Δx)˙=\frac d{dt}(x_0+Δx(t))&=y_0\quad+\quad Δy \\ \\ (Δy)˙=\frac d{dt}(y_0+Δy(t)) &=(x_0+Δx)+(x_0+Δx)^2−(y_0+Δy) \\ &=x_0+x_0^2-y_0\quad+\quad (1+2x_0)Δx-Δy\quad+\quad Δx^2 \end{align}

  • 1
    $\begingroup$ I do not see why you get $y_0+\Delta y$ for the first equation. $\endgroup$ – Rhjg Jan 3 '16 at 13:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.